Mechanism of Sedimentary Basin Formation : Multidisciplinary Approach on Active Plate Margins - Itoh, Yasuto; Itoh, Yasuto (IntechOpen, 2013)
This book is devoted to the mechanisms of sedimentary basin formation on active plate margins, which show enormous diversity reflecting complex tectonic processes. Multidisciplinary approach pursuing basin-forming mechanism is based on geology, sedimentology, geochronology and geophysics. Some chapters are dedicated to the genetic analysis of sedimentary basins in wrench deformation zones in forearc and intra-arc regions. Another block of chapters deals with basin formation in peripheral regions of Eurasia and intra-arc / foreland basins under the influence of the fluctuation of stress regimes. Finally geophysical approaches to basin analyses are shown in some chapters from microscopic to regional scales. Diverse contents of the chapters provide the audience with the present accomplishments of basin researches on active margins by Earth scientists.
English
Keywords: Soil science, sedimentology; Soil science, sedimentology